1990
DOI: 10.1021/j100379a053
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization tendency of 1-alkanols and hydrophobic interaction in sodium lauryl sulfate in ordinary water, heavy water, and urea solutions

Abstract: 6445dehydration may be required to account for this. The present study, as shown above, provides us some evidence to indicate the structure of acid sites included in silica-alumina and silica-coated alumina. First, we can conclude that the silica on alumina does not possess such acid sites as found in the silica-alumina catalyst. In other words, silanol attached to AI does not show strong Bransted acidity. This is in agreement with the conclusion by Kawakami et al. on the basis of the quantumchemical cal~ulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…2b are given in Table 2. In the range of urea concentrations from 0 to 5 M, where comparison is possible, the values obtained here are in very good agreement with literature values derived from specific conductance measurements (5). A notable aspect of the results shown in Fig.…”
Section: Cussion For the Purpose Of This Work It Is Important Onlysupporting
confidence: 90%
See 2 more Smart Citations
“…2b are given in Table 2. In the range of urea concentrations from 0 to 5 M, where comparison is possible, the values obtained here are in very good agreement with literature values derived from specific conductance measurements (5). A notable aspect of the results shown in Fig.…”
Section: Cussion For the Purpose Of This Work It Is Important Onlysupporting
confidence: 90%
“…It has been found that urea (A) increases the criti-Similarly, urea was assumed to be a nonpenetrating agent cal micelle concentration of ionic (1, 4-7, 12, 15-17) and in a study performed by Gonzalez et al (12) on the effect nonionic (1,2,7,9) surfactants; (B) decreases the micellar of additives on the solubility of naphthalene derivatives in size of ionic (8,14,17) and nonionic (9) surfactants; (C) micellar solutions. Alternatively, results from recent studies increases the counterion dissociation degree of ionic micelles have been interpreted in favor of a direct mechanism of urea (5,8,15,16); (D) increases the cloud point of nonionic action on properties of micelles (1-4, 13, 15, 17). Most of the studies concluding that urea acts according to the direct 1 To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miyaghisi et al (11) performed a study of proteins (15) and alters several properties of micellar of the alteration in properties of micelles induced by pertursolutions: (A) it increases the critical micelle concentration bation in the external environment and used urea as an addiof ionic (1,5,7,9) and nonionic (1,2,6,9) surfactants; tive assumed to be unable to penetrate the micelles. Simi-(B) it decreases the micellar size of ionic (8,14) and non-larly, urea was assumed to be a nonpenetrating agent in a ionic (6) surfactants; (C) it increases the counterion dissoci-study performed by Gonzalez et al (12) regarding the effect ation degree of ionic micelles (5,7,8); (D) it increases the of additives on the solubility of naphthalene derivatives in cloud point of nonionic (2,6) and decreases the cloud point micellar solutions. Alternatively, results from recent studies of zwitterionic (10) surfactants; (E) it increases the local have been interpreted to favor a direct mechanism of urea viscosity and decreases the local polarity at the micellar action upon properties of micelles.…”
Section: Introductionmentioning
confidence: 99%
“…[30] The reactivity of 1 strongly decreases on going from water to organic solvents, [39] which may be partly due to a decrease in the dielectric constant of the media, but alcohols are known to influence the dielectric constant within micelles, [38] as well as influencing other key properties. [43][44][45] …”
Section: Entrymentioning
confidence: 99%